Effects of NXY-059 in experimental stroke: an individual animal meta-analysis. - Bath, P; Gray, L; Bath, A; Buchan, A; Miyata, T; Green, A (2009)
BACKGROUND AND PURPOSE: Disodium 2,4-disulphophenyl-N-tert-butylnitrone (NXY-059) was neuroprotective in experimental stroke models but ineffective in a large clinical trial. This first-ever individual animal meta-analysis was used to assess the preclinical studies. EXPERIMENTAL APPROACH: Studies were obtained from AstraZeneca and PubMed searches. Data for each animal were obtained from the lead author of each study and/or AstraZeneca. Published summary data were used if individual data were not available. Infarct volume and motor impairment were standardized to reflect different species and scales. Standardized mean difference (SMD), coefficients from multilevel models and 95% confidence intervals (95% CI) are presented. KEY RESULTS: Fifteen studies (26 conditions, 12 laboratories) involving rats (544), mice (9) and marmosets (32) were identified (NXY-059: 332, control: 253) with individual data for 442 animals. Four studies were unpublished. Studies variably used randomization (40%), blinding of surgeon (53%) and outcome assessor (67%). NXY-059 reduced total (SMD -1.17, 95% CI -1.50 to -0.84), cortical (SMD -2.17, 95% CI -2.99 to -1.34) and subcortical (-1.43, 95% CI -2.20 to -0.86) lesion volume; efficacy was seen in transient, permanent and thrombotic ischaemia, up to 180 min post occlusion. NXY-059 reduced motor impairment (SMD -1.66, 95% CI -2.18 to -1.14) and neglect. Evidence for performance, attrition and publication bias was present. CONCLUSIONS AND IMPLICATIONS: NXY-059 was neuroprotective in experimental stroke although bias may have resulted in efficacy being overestimated. Efficacy in young, healthy, male animals is a poor predictor of clinical outcome. We suggest the use of preclinical meta-analysis before initiation of future clinical trials.